Running virtual meetings : test your technology, keep their attention, connect across time zones. - Harvard Business Review Press (Boston, Massachusetts : Harvard Business Review Press, 2016)
Whether you're hosting a conference call or running a WebEx meeting, virtual meetings are ripe for problems. Poor call quality, people forgetting to mute, people staying muted rather than participating--the list of things that can and do go wrong is endless. But you can prepare and lead an effective meeting from afar. This book will quickly bring you up to speed. With guiding principles and tips for making your virtual meeting run smoothly, you'll tick through every item on your agenda. Running Virtual Meetings guides you through the basics of: - Conducting efficient and productive virtual meetings - Preparing for a successful meeting--from crafting a realistic agenda to performing a technological test-drive - Managing common problems, such as connectivity issues, low talkers, blowhards, and background noise - Following up and holding people accountable when your attendees are spread all over the globe.--
What is a virtual meeting? -- What are the key challenges? -- Why hold one? -- What this book will do -- Plan your meeting -- Decide if you need to meet -- Create an agenda -- Identify the participants -- Pick a platform -- Set a time -- Manage the technology -- Assess your needs -- Choose your tools -- Test your set-up -- What to do when technology fails -- Set expectations for participation -- Assign roles -- Establish meeting processes -- Clarify etiquette -- Send your invitation and materials -- Conduct the meeting -- Just before the meeting starts -- Open the meeting -- Facilitate the discussion -- Control the tone -- Close the meeting -- Follow up -- Navigate special situations -- Give a video presentation -- Bridge linguistic or cultural barriers.
Includes bibliographical references (pages 115-117) and index.
Keywords: Teleconferencing -- Handbooks, manuals, etc; Business meetings -- Management -- Handbooks, manuals, etc; Business meetings -- Technological innovations -- Handbooks, manuals, etc